Evoluzione della chirurgia sostitutiva di ginocchio - Cerulli, G. (Lo Scalpello - Journal, 2019)
THE EVOLUTION OF KNEE-REPLACEMENT The advent of knee arthroplasty is one of the most significant advances in surgery. Engineering and biomechanical innovations have shown a fast and effective evolution, in order to satisfy increasing functional requirements. In this paper, the most important steps of this fascinating story are presented. It is clear that biomechanical and tribological studies have always represented the basis for the onset of minimally invasive surgery, with less complications and greater patient satisfaction. This evolution concerns not only the design of components, but also the materials used.